Effects of sensory feedback in intra-oral target selection tasks with the tongue. - Caltenco, Hector A.; Lontis, Eugen R.; Bentsen, Bo; Andreasen Struijk, Lotte N. S. (Disability & Rehabilitation: Assistive Technology, 2013)
Purpose: To investigate the effects of visual and tactile intra-oral sensor-position feedback for target selection tasks with the tip of the tongue. Method: Target selection tasks were performed using an inductive tongue-computer interface (ITCI). Visual feedback was established by highlighting the area on a visual display corresponding to the activated intra-oral target. Tactile feedback was established using a sensor-border matrix over the sensor plates of the ITCI, which provided sensor-position tactile queues via the user's tongue. Target selection tasks using an on-screen keyboard by controlling the mouse pointer with the ITCI's was also evaluated. Results: Mean target selection rates of 23, 5 and 15 activations per minute were obtained using visual, tactile and 'none' feedback techniques in the 3rd training session. On-screen keyboard target selection tasks averaged 10 activations per minute in the 3rd training session. Involuntary activations while speaking or drinking were significantly reduced either through a sensor-matrix or dwell time for sensor activation. Conclusions: These results provide key design considerations to further increase the typing efficiency of tongue-computer interfaces for individuals with upper-limb mobility impairments.